Wintering Town: Individual Quality of Migratory Warblers Using Green Urban Areas in a Neotropical City - Pacheco-Muñoz, Rodrigo; Ceja-Madrigal, Adrián; Pérez-Negrón, Edgar; Ortiz-Asbun, A. Karen; Schondube, Jorge E. (Frontiers in Ecology and Evolution, 2022)
Migratory birds can be familiar winter visitors of Neotropical cities. However, of the regional migrant species bird pool, only a few species are abundant in urban areas. Their presence inside cities has been positively related to green urban areas with high tree cover. However, urban elements like artificial lights can also attract them to cities. Habitat quality that enables energetic refueling for migrant birds is crucial in all their annual migratory stages. While some Nearctic cities offer a high-quality refueling habitat for migrant birds, we lack this information for Neotropical cities where migratory birds winter. In this study, we evaluate whether the urban green areas of a Neotropical city act as high-quality habitats for two abundant species of migratory warblers: Setophaga coronata and Leiothlypis ruficapilla. We assessed this by capturing birds inside three urban green areas and comparing their abundances, population structure, and individual quality (scale mass index - SMI) with individuals spending winter in natural vegetation habitats outside the city. We found that both species do not show differences in SMI between urban and non-urban sites. We also found that Setophaga coronata had a higher capture rate in urban than non-urban sites, while Leiothlypis ruficapilla had similar capture rates in both habitats. Our findings indicate that the urban green areas of cities can act as suitable quality habitat during winter for two abundant migrant birds. Our results indicate that cities can have a higher conservation potential for a declining and sensitive group such as the Nearctic-Neotropical migratory birds than previously thought. We also point out the need to acknowledge that migratory species can be urban dwellers.